Perception and prevalence of sleep paralysis among adults of a Newar community in Bhaktapur district. - Kakshyapati,Nishtha (2018)
ABSTRACT: Introduction: Sleep paralysis is an experience of being temporarily unable to move or talk during the transitional periods between sleep and wakefulness. There are 3 categories of hallucination. Intruder hallucination consists of sense of evil presence in the room, incubus hallucination describes a sensation of pressure on chest and feelings of being suffocated. The 3rd category includes vestibular-motor hallucination consisting of illusory movement experiences such as floating above the bed. Objectives: To assess the perception and prevalence of sleep paralysis among the adults of a Newar community. Methodology: Descriptive cross sectional study design was conducted among 118 adults of a newar community. Semi-structured questionnaire was used for data collection. Data was collected using interview technique and analyzed using SPSS Version 16. Findings: The findings revealed that 63.6% of the respondents called the phenomenon of sleep paralysis as "attack of a khyaak" in their local perception. Less than half (41%) of the respondents answered the cause of sleep paralysis to be medical, 21% answered supernatural cause, 64.8% of them think that episode of sleep paralysis can be prevented. Similarly, half of the respondents (50%) think that the episode can be interrupted during its event. 74.3% of them think that sleep paralysis affects our daily life. The prevalence of sleep paralysis was 56.2%. Gender was associated with prevalence of sleep paralysis (p=0.006) Conclusion: The common name for sleep paralysis in a newar community came to be "attack of a khyaak" in their local language. As most of the respondents shared the cause of sleep paralysis to be medical related, the measures of prevention and interruption were related to health rather than superstitious beliefs. Most of the respondents thought sleep paralysis can be prevented by maintaining body posture while sleeping, taking support from doctor. However, people also thought that the phenomenon can be prevented by chanting mantras before sleeping, using ashes in the forehead before sleep. According to most of them, the phenomenon can be interrupted by extremely moving the parts of body and shouting out loud. Keywords: sleep paralysis, perception, prevalence